Современное медиаискусство в контексте вертикального структурирования культуры - Косюк, Оксана Михайлівна; Kosiuk, O. M. (Алтайский государственный университет, 2011)
Дан анализ проблемы вертикального структурирования культуры в контексте современного медиапространства на фоне эстетико-коммуникативных поисков человечества. Tthe article deals in brief with the problem of vertical structure of culture in the context of the modern mediaspace on the basis of aesthetic human search.
Modern media art in the context ofvertical structuring of culture
Keywords: релаксационный код культуры; стратификация развлечений; вертепная традиция; пародирование; техногенные аналогии; relaxational cod of culture; stratification of entertainments; Nativity Play tradition; parodying; understudying; technological analogues; durable paradigms